Technical report on the pilot scale-up of the improved cassava variety SM4989-4 (Biofortified yellow cassava) - Taborda Andrade, Luis Alejandro; Gonzalez, Carolina; Fenstemaker, Sean (2025)
This report summarizes a pilot scale-up initiative to evaluate the feasibility of scaling the biofortified cassava variety SM4989-4 through processed cassava value chains in Colombia, in response to its limited acceptance in the fresh market. The pilot combined industrial processing trials and seed multiplication tests with selected private-sector partners. Processing results showed that SM4989-4 was not suitable for croquette production due to cooking time limitations but performed well in chip processing and showed promising potential for cassava flour targeting export-oriented markets. These trials generated direct technical evidence and reduced uncertainty for private-sector decision-making. Seed multiplication pilots implemented across multiple regions resulted in concrete investment commitments and demonstrated the practicality of scaling SM4989-4 when aligned with specific processing applications. Overall, the pilot confirms that processed value chains offer a viable and efficient pathway for scaling biofortified cassava, providing a strong foundation for targeted market expansion and future investment.